Correlation of Severity of Coronary Artery Disease with Urine Microalbumin in Indian subjects using Gensini score - VH, Kiran; BC, Mahadevaswamy; kamath, Padmanabha (International Journal of Medical Research and Review, 2015)
Background: Microalbuminuria is one of the simple and independent risk factor for Coronary artery disease. The study was aimed to study the severity of Coronary artery disease with degree of Microalbuminuria using Gensini scoring. Methodology: Our study consisted of 233 subjects admitted for coronary angiography .All subjects were asked detailed medical history mainly concentrating on important risk factors like Diabetes, Hypertension and physical examination was thoroughly carried out; detection of urine Microalbumin and Coronary angiography was carried on. Gensini scoring was used to assess the severity of CAD. Results: Out of 233 subjects which were studied, 140 were diabetics (60.1%). 95% of Diabetics had abnormal Gensini score, which is statistically significant (p=0.004<0.01), 84% of Non diabetic subjects had abnormal Gensini score (suggests CAD), with odds ratio 3.6 (CI 1.4 to 9.3). Diabetics had a mean age of 60years and Non Diabetics is 58years in our study. There was good correlation between Microalbuminuria and Gensini score with r= +0.510 (p=0.0001) and also good correlation between Diabetes duration and Gensini score with r= +0.626 (p=0.0001). Conclusion: Severity of CAD as assessed by Gensini score was higher in patients with higher microalbuminuria.